2008
DOI: 10.2215/cjn.02990707
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Facility Characteristics and Variation in Employment Rates

Abstract: Background: Investigation of factors associated with variation in dialysis patient employment has focused primarily on patient-level factors. Little is known about facility-level factors that may be associated with patient employment.Design, setting, participants, and measurements: The ESRD Facility Survey (CMS-2744A) began in 2004 to collect counts of employed patients aged 18 to 54, in addition to dialysis unit census, types and timing of treatments offered, and staffing. Using the 2004 ESRD Facility Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 14 publications
2
75
1
5
Order By: Relevance
“…In contrast, those who had not retained the same level of employment from 6 months before kidney failure were more likely to choose HD. Although it could be argued that those chose PD were more educated and more motivated to keep their employment, this finding is consistent with findings from previous studies (13,14). In general, PD allows more flexibility and control over one's treatment schedule and is associated with higher patient satisfaction than in-center hemodialysis (15,16).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, those who had not retained the same level of employment from 6 months before kidney failure were more likely to choose HD. Although it could be argued that those chose PD were more educated and more motivated to keep their employment, this finding is consistent with findings from previous studies (13,14). In general, PD allows more flexibility and control over one's treatment schedule and is associated with higher patient satisfaction than in-center hemodialysis (15,16).…”
Section: Discussionsupporting
confidence: 90%
“…The analyses that we report do not include facility-level factors that may influence patients' employment, although the analyses do take into account the effect of patient clustering in facilities as a result of the sampling design. We previously showed that dialysis clinic-specific employment rates are positively associated with availability of a late (5 p.m. or later) HD treatment shift, availability of PD or home HD training, and provision of frequent HD and that in facilities with the highest employment rates, patients are more likely to receive vocational rehabilitation services (19).…”
Section: Discussionmentioning
confidence: 99%
“…Most people can earn much more money by working than they would receive from disability, however. Vocational counselors can help individuals who require dialysis with decisions about balancing the financial rewards that they can expect from employment versus receipt of disability benefits (18), and dialysis facilities with the highest employment rates are more likely to have patients who receive vocational rehabilitation services (19). Under the Ticket to Work and Work Incentives Improvement Act of 1999, people may be able to retain Medicaid coverage when they become employed.…”
Section: Discussionmentioning
confidence: 99%
“…We are unable to further define an answer for the question of whether dialysis choice influences employment status or if employment status influences dialysis choice. This question was recently explored elsewhere (16,21). Age may or may not be associated with working status.…”
Section: Discussionmentioning
confidence: 99%